Professionals’ views of fetal monitoring during labour: a systematic review and thematic analysis - Smith Valerie; Begley Cecily M; Clarke Mike; Devane Declan (BMC Pregnancy and Childbirth, 2012)
Abstract Background Current recommendations do not support the use of continuous electronic fetal monitoring (EFM) for low risk women during labour, yet EFM remains widespread in clinical practice. Consideration of the views, perspectives and experiences of individuals directly concerned with EFM application may be beneficial for identifying barriers to and facilitators for implementing evidence-based maternity care. The aim of this paper is to offer insight and understanding, through systematic review and thematic analysis, of research into professionals’ views on fetal heart rate monitoring during labour. Methods Any study whose aim was to explore professional views of fetal monitoring during labour was considered eligible for inclusion. The electronic databases of MEDLINE (1966–2010), CINAHL (1980–2010), EMBASE (1974–2010) and Maternity and Infant Care: MIDIRS (1971–2010) were searched in January 2010 and an updated search was performed in March 2012. Quality appraisal of each included study was performed. Data extraction tables were developed to collect data. Data synthesis was by thematic analysis. Results Eleven studies, including 1,194 participants, were identified and included in this review. Four themes emerged from the data: 1) reassurance, 2) technology, 3) communication/education and 4) midwife by proxy. Conclusion This systematic review and thematic analysis offers insight into some of the views of professionals on fetal monitoring during labour. It provides evidence for the continuing use of EFM when caring for low-risk women, contrary to current research evidence. Further research to ascertain how some of these views might be addressed to ensure the provision of evidence-based care for women and their babies is recommended.